Freeze-thaw stability of Pickering emulsions stabilized by soy protein nanoparticles. Influence of ionic strength before or after emulsification. (January 2018) - Zhu, Xue-Feng; Zheng, Jie; Liu, Fu; Qiu, Cao-Ying; Lin, Wei-Feng; Tang, Chuan-He
Abstract: There is still a debate about the influence of salts on the freeze-thaw stability of emulsions. In this research, the influence of the NaCl addition (before or after the emulsification; 100–500 mM) on the freeze-thaw stability of the Pickering emulsions stabilized by heat-induced soy protein isolate (SPI) nanoparticles, at a given protein concentration of 1.0% (w/v) and oil fraction of 0.4, was investigated. The addition of NaCl resulted in considerable changes in particle characteristics (including particle size, surface hydrophobicity and ζ -potential) of the SPI nanoparticles, with the extent of the changes varying with the applied ionic strength ( μ ). Despite the NaCl addition before or after the emulsification, the presence of NaCl remarkably improved the freeze-thaw stability against droplet coalescence and creaming of the emulsions, though the improvement was related to the applied μ . The improvement of the freeze-thaw stability would be largely attributed to the strengthening of the interfacial protein or protein nanoparticle films coating droplets, rather than the inhibition of ice crystal formation by the presence of NaCl. If the salt was introduced before the emulsification, a gel-like network might be formed in the corresponding emulsions, which would further provide an additional stabilization against the freeze-thaw treatment. Optimal freeze-thaw stability was observed in the presence of appropriate concentrations of NaCl (e.g., 100–200 mM). This is the first report to indicate the importance of the electrostatic screening to the improvement of the Pickering emulsions stabilized by charged particles. The findings would be of great importance for the formulation of food grade emulsions with excellent freeze-thaw stability. Graphical abstract: Highlights: The influence of NaCl addition on the freeze-thaw stability of the SPI Pickering emulsions was investigated. The presence of NaCl remarkably improved the freeze-thaw stability. The improvement of the freeze-thaw stability was largely due to the strengthening of interfacial films. The formation of a gel-like network could provide an additional stabilization towards freeze-thaw treatment. This is the first report to indicate the importance of electrostatic screening to the freeze-thaw stability of Pickering emulsions.